(untitled) (Nexo Revista Científica, 2020)
Bazhenov Formation is regarded as the main oil-bearing stratum mothering nearly all the fields of the Western Siberia Oil-Gas-bearing Megabasin. Presently, it is one of the most studied formations of Siberia and, probably, Eurasia as a whole. While there is an enormous amount of studies devoted to the Bazhenov Formation, there are no detailed mineralogical studies at the modern hardware level. The age and sources of the terrigenous materials of the formation have not been studied as well. We have explored the detrital monazite from the upper-Jurassic terrigenous sediments of the Multan Area at the foundation of the Bazhenov Formation in the central part of Western Siberia, Surgut District. All the detrital rare earth phosphate is of the cerium kind being a monazite-(Се). The mineral is rather dissimilar in respect of its chemical properties, especially, the content of thorium. Some fragments have been subjected to superposed secondary changes. The detrital monazite is rounded to various degrees which is indicative of the various distances from the rare earth phosphate orebody washout. As per the chemical data, most of the monazite has been washed out from the medium and basic rocks (probably subalkaline or alkaline) as well as the sialic rocks (granitoids and associated veins). According to the chemical dating, most of the monazite fragments have been washed out of the very ancient Proterozoic formations and lower-Proterozoic rocks. Terrigenous materials derives probably from the rock assemblages of the eastern and south-eastern fringes of the Western Siberian megabasin such as the Proterozoic Yenisei Ridge or Lower-Proterozoic blocks of the Altay and Sayan Faulting.